Delayed response : the art of waiting from the ancient to the instant world - Farman, Jason, 1977- (Yale University Press, 2018)
We have always been conscious of the wait for life-changing messages, whether it be the time it takes to receive a text message from your love, for a soldier's family to learn news from the front, or for a space probe to deliver data from the far reaches of the solar system. In this book in praise of wait times, award-winning author Jason Farman passionately argues that the delay between call and answer has always been an important part of the message. Traveling backward from our current era of Twitter and texts, Farman shows how societies have worked to eliminate waiting in communication and how they have interpreted those times' meanings. Exploring seven eras and objects of waiting--including pneumatic mail tubes in New York, Elizabethan wax seals, and Aboriginal Australian message sticks--Farman offers a new mindset for waiting. In a rebuttal to the demand for instant communication, Farman makes a powerful case for why good things can come to those who wait.